State Space Examples
State Space Examples
D
x0
1.3 EXAMPLES
y(t)
m f(t)
c
ky(t)
m f (t)
cy(t)
y(t) = x1 (t)
u(t) = f (t)
x1 (t) = iL (t)
x2 (t) = v(t)
1
x2 (t) + x1 (t) + C ẋ2 (t) = u(t)
R
These relationships can be rearranged so as to isolate state-variable
time derivatives as follows:
1
ẋ1 (t) = x2 (t)
L
1 1 1
ẋ2 (t) = − x1 (t) − x2 (t) + u(t)
C RC C
iL(t) +
i(t) R L C v(t)
−
Here, the energy-storage elements are the two springs and the two masses.
Defining state variables in terms of mass displacements and velocities
10 INTRODUCTION
y1(t) y2(t)
f(t)
k1 k2 c
m1 m2
yields
x1 (t) = y1 (t)
x2 (t) = y2 (t) − y1 (t)
x3 (t) = ẏ1 (t)
x4 (t) = ẏ2 (t)
we could have defined the second state variable based on the absolute
mass displacement, that is x2 (t) = y2 (t), and derived an equally valid
state-space representation. Making this one change in our state variable
definitions, that is,
x1 (t) = y1 (t)
x2 (t) = y2 (t)
x3 (t) = ẏ1 (t)
x4 (t) = ẏ2 (t)
yields the new A and C matrices
⎡ ⎤
0 0 1 0
⎢ 0 0 0 1 ⎥
⎢ ⎥
⎢ (k + k2 ) k2 ⎥
A = ⎢− 1 0 0 ⎥
⎢ m1 m1 ⎥
⎣ k2 −k2 c ⎦
0 −
m2 m2 m2
1 0 0 0
C=
0 1 0 0
The B and D matrices are unchanged.
In addition, Kirchoff’s current law applied at the top node of the induc-
tor gives
iL (t) = i1 (t) − i2 (t)
12 INTRODUCTION
+ vC1(t) − + vC2(t) −
R1
C1 C2
vin(t) + iin(t)
L iL(t) R2
−
i1(t) i2(t) i3(t)
Calculating and multiplying through by the inverse and yields the state
differential equation, that is,
⎡ 1 −1 R2 ⎤
⎡ ⎤ ⎢ (R1 + R2 )C1 (R1 + R2 )C1 (R1 + R2 )C1 ⎥ ⎡ ⎤
ẋ1 (t) ⎢ ⎥ x1 (t)
⎢ −1 −1 −R ⎥
⎣ ẋ2 (t) ⎦ = ⎢ 1 ⎥ ⎣ x2 (t) ⎦
⎢ (R + R )C + + ⎥
ẋ3 (t) ⎢ 1 2 2 (R 1 R 2 )C 2 (R 1 R 2 )C 2 ⎥ x3 (t)
⎣ −R2 R1 −R1 R2 ⎦
(R1 + R2 )L (R1 + R2 )L (R1 + R2 )L
⎡ 1 −R2 ⎤
⎢ (R1 + R2 )C1 (R1 + R2 )C1 ⎥
⎢ ⎥
⎢ 1 −R2 ⎥ u1 (t)
+⎢⎢ ⎥
⎥
⎢ (R1 + R2 )C2 (R1 + R2 )C2 ⎥ u2 (t)
⎣ R2 R1 R2 ⎦
(R1 + R2 )L (R1 + R2 )L
which is in the required format from which coefficient matrices A and B
can be identified. In addition, the associated output equation y(t) = Lẋ3 (t)
can be expanded to the algebraic output equation as follows
⎡ ⎤
x1 (t)
−R2 R1 −R1 R2
y(t) = ⎣ x2 (t) ⎦
(R1 + R2 ) (R1 + R2 ) (R1 + R2 ) x (t) 3
R2 R1 R2 u1 (t)
+
(R1 + R2 ) (R1 + R2 ) u2 (t)